Neural Correlates of Semantic Inhibition in Relation to Hypomanic Traits: An fMRI Study - Raucher-Chéné, Delphine; Terrien, Sarah; Gierski, Fabien; Obert, Alexandre; Caillies, Stéphanie; Besche-Richard, Chrystel; Kaladjian, Arthur (Frontiers in Psychiatry, 2018)
Objectives Language modifications are a core feature of mania, but little is known about the semantic mechanisms behind these disturbances. The aim of the present study was thus to identify deficits in semantic inhibition and their respective neural activation patterns in a sample of individuals assessed for hypomanic personality traits. Methods Thirty-six young adults with no neurological or psychiatric diagnoses were assessed for hypomanic personality traits with the Hypomanic Personality Scale (HPS) and underwent an fMRI task of semantic ambiguity resolution. Results Regression analyses revealed a positive association between the HPS score and activity in the left superior frontal gyrus, left inferior parietal lobule, and anterior cingulate gyrus during semantic ambiguity resolution. Conclusions We found a link between HPS scores and brain areas that are part of the cognitive control loop and semantic memory network during language processing in a nonclinical sample of individuals. The hyperactivation of these regions may reflect a compensatory neural response in a population with greater vulnerability to BD. Conclusions We found a link between HPS scores and the pattern of brain activation during language processing in a nonclinical sample of individuals, supporting the notion that semantic inhibition processes constitute potential vulnerability markers for BD. Further research, in the form of longitudinal studies or studies among unaffected relatives of patients with BD, could yield further supporting evidence and provide leads for the earlier diagnosis and treatment of the disease.